2005
DOI: 10.1002/jbm.b.30427
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical integrity of the implant–bone interface with BoneWelding® technology: Determination of quasi‐static interfacial strength and fatigue resistance

Abstract: The BoneWelding technology is an innovative bonding method, which offers new alternatives in the treatment of fractures and other degenerative disorders of the musculoskeletal system. The BoneWelding process employs ultrasonic energy to liquefy a polymeric interface between orthopaedic implants and the host bone. Polymer penetrates the pores of the surrounding bone and, following a rapid solidification, forms a strong and uniform bond between implant and bone. Biomechanical testing was performed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
6
21
0
Order By: Relevance
“…The introduction of Sonic Weld with biodegradable plates claiming that it will augment the mechanical properties and fracture stability giving the opportunity to replace the metallic plates in fixation of mandibular fracture [13]. However little literature are available on this point and so accordingly we planned this study to evaluate using of ultrasound based welding process for fixation of biodegradable plates in pediatric mandibular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of Sonic Weld with biodegradable plates claiming that it will augment the mechanical properties and fracture stability giving the opportunity to replace the metallic plates in fixation of mandibular fracture [13]. However little literature are available on this point and so accordingly we planned this study to evaluate using of ultrasound based welding process for fixation of biodegradable plates in pediatric mandibular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases the complete fragment did not heal and the osteotomy gap was still visible. Ferguson et al 36 demonstrated greater anchoring of ultrasound-activated pins, compared with non-ultrasound-activated, resorbable implants. But their biomechanical tests were performed without the effect of synovial fluid and direct shear forces.…”
Section: Discussionmentioning
confidence: 99%
“…The BoneWelding ® technology is an ultrasound-based method to anchor bioresorbable plates and meshes to the bone using thermoplastic polymer pins . Due to ultrasonic vibrations, the polymer is temporarily liquefied, filling the cavities of spongious bone and improving the anchoring compared to conventional screw systems (Eckelt et al, 2007;Ferguson et al, 2006;Pilling et al, 2007). Different preclinical studies (Arnoldi et al, 2012;Heidenreich et al, 2011;Langhoff et al, 2009) describe the use of 70/30 poly(L-lactide-co-D, L-lactide) with the BoneWelding ® technology.…”
Section: Introductionmentioning
confidence: 97%